(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
This study provides an integrated investigation of the sedimentology, facies architecture, and palaeoenvironmental evolution of the Ajali Sandstone and Mamu Formation in the northern Anambra Basin, southeastern Nigeria. Detailed fieldwork along the Iyale–Agbenema corridor combined stratigraphic logging, granulometric analysis, petrographic studies, and heavy mineral characterization with facies classification and palaeoenvironmental reconstruction. The Ajali Sandstone is composed predominantly of medium– to coarse–grained, poorly sorted quartz arenites, characterized by prominent cross-bedding, flaser structures, herringbone cross-stratification, and Skolithos burrows. Grain-size parameters, C–M patterns, and linear discriminant functions collectively indicate deposition in tidally influenced fluvial–deltaic systems, shaped by alternating phases of high-energy braided river discharge and nearshore marine reworking. Petrographic evidence, complemented by heavy mineral assemblages enriched in zircon, tourmaline, and rutile, suggests high textural maturity and points to multicycle sediment recycling sourced from uplifted basement complexes and recycled sedimentary terranes. In contrast, the Mamu Formation is dominated by laminated clays, siltstones, shales, and ferruginised horizons bearing root traces and plant debris. These facies reflect deposition within lower delta plain to prodelta environments, marked by fluctuating redox conditions, quiet-water sedimentation, and episodic subaerial exposure. Together, the Ajali–Mamu successions capture the complex interplay of Late Cretaceous transgressive–regressive cycles in southeastern Nigeria, where proximal braided fluvial systems repeatedly prograded into coastal plain and shallow marine environments. The integration of sedimentological, petrographic, and provenance data highlights this succession as a key stratigraphic archive for reconstructing basin evolution, sediment dispersal pathways, and palaeoenvironmental dynamics within the Benue Trough system. Overall, these findings refine existing depositional models and underscore the controlling role of tidal–fluvial interactions in shaping the sedimentary architecture of paralic basins during the Late Cretaceous.